REVIEW ON OPPORTUNITIES AND CONSTRAINTS OF INDUSTRIAL DEVELOPMENT ON ECONOMIC GROWTH IN ETHIOPIA - Alemayehu Oljira Wolde; Fenet Belay (Socio-Economics/Agribusiness Department, 2019)
This paper is designed to review opportunities, constraints and contributions of industrial development on economic growth in Ethiopia. Sources such as scholarly publication, News and magazines, Books and chapters, Conference proceedings, government documents, theses and Dissertations have been reviewed. The review result indicates that industrial sector have substantial contribution to economic growth that helps to create a large portion of the resources needed to fund social development programs in the country. In addition, creation of employment and hence generation of income take place in the sector directly and are indirectly fostered in other sectors like agriculture or services through their linkages to industry. However, financial constraints, shortage of raw materials supply and lack of skilled manpower were identified as the main obstacles to the development of the sector. Finally the review argues that high rate of capital accumulation is a necessary condition for bringing about structural transformation and increased level of production and productivity to give rise for industrialization and the use of appropriate combination of skilled manpower, modern and suitable technologies and investment on both public infrastructures and manufacturing activities should be made.